Pro-inflammatory cytokine (IL-1β and IL-6) response in goats challenged with Corynebacterium pseudotuberculosis and its immunogen Mycolic Acids - Abdullah, Faez Firdaus Jesse; Mohammed Naji, Ahmed Odhah; Mohd Lila, Mohd Azmi; Saad, Mohd Zamri; Haron, Abd Wahid; Hambali, Idris Umar; Mahmood, Zaid Khudher (Science Publications, 2017)
The causative agent of Caseous Lymphadenitis (CLA) is Corynebacterium pseudotuberculosis. A chronic disease of sheep and goats which is mainly characterized by suppurative abscesses in both superficial and visceral lymph nodes. There is paucity of information on the proinflammatory cytokine (IL-1β and IL-6) responses due to C. pseudotuberculosis and Mycolic Acid (MAs) inoculation in goats. Therefore, this study was conducted to evaluate the immunogenicity of C. pseudotuberculosis and MAs. Twelve clinically healthy crossbred Boer female goats were divided into 3 groups; A, B and C with 4 goats per group. The A group was injected with 2 mL sterile Phosphate Buffered Saline (PBS) intradermally as negative control group while B group was inoculated with 2 mL of MAs extract intradermally. Group C was inoculated with 2 mL 1×109 colony forming unit (cfu) of live C. pseudotuberculosis intradermally. Blood was collected from the jugular vein periodically for IL-1β and IL-6 analysis throughout the experimental period. The results showed significant increase (p<0.05) in IL-1β concentration in weeks two, three, four, five, six, eight, nine and ten in C. pseudotuberculosis inoculated group, whilst in MAs inoculated group, IL-1β concentration increased significantly (p<0.05) in weeks three, five, six, eight, nine and ten compared to the control. However, IL-1β showed significant decrease (p<0.05) in week twelve in both treated groups. The concentration of IL-6 was significantly increased (p<0.05) in weeks five, six, seven and eight in C. pseudotuberculosis inoculated group compared to the control, whilst MAs inoculated group indicated a significant increase (p<0.05) in weeks two, three, four, five, six and eight compared to the control. Therefore, this study concluded that MAs extracted from C. pseudotuberculosis has immunogenic properties represented by all the significant changes in concentration of IL-1 β and IL-6.